Effects of Mobile-Assisted Language Learning on EFL/ESL Reading Comprehension - Li, Rui (Educational Technology ＆ Society, 2022)
While an increasing number of studies have cast light on the effectiveness of MALL (mobile-assisted language learning) on English as a foreign/second language (EFL/ESL) reading comprehension, there is still a lack of comprehensive meta-analysis regarding the effect sizes of these studies. To fill the gap, this study reported results based on a meta-analysis of 20 effect sizes from 17 experimental and quasi-experimental studies published during 2000-2020. The results showed that the overall effect size was significantly large, suggesting the use of MALL applications for EFL/ESL reading comprehension is more effective than traditional methods. The moderating effects of eight moderators were analyzed. The intervention settings and intervention durations were found to be significant moderators, while others did not find a significant moderating effect. Implications of the findings were discussed.